2017
DOI: 10.1159/000480422
|View full text |Cite
|
Sign up to set email alerts
|

The “Molecularly Unstratified” Patient: A Focus for Moral, Psycho-Social and Societal Research

Abstract: The biomedical paradigm of personalised precision medicine -identification of specific molecular targets for treatment of an individual patient -offers great potential for treatment of many diseases including cancer. This article provides a critical analysis of the promise, the hype, and the pitfalls attending this approach. In particular, we focus on "molecularly unstratified" patients -those who, for various reasons, are not eligible for a targeted therapy. For these patients, hope-laden therapeutic options … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Of course, the prospect of therapeutic benefit will still vary considerably between trials according to phase (I-III), disease, and therapeutic mechanism (e.g., cytotoxics, targeted therapeutics, immunotherapeutic, and combination approaches), and, even within therapeutically oriented trials, every participant could not expect to benefit. 98 Nevertheless, patients considering participation in modern clinical trials, including earlyphase designs, might now be affirmed, at least to some extent, in expectations of benefit from trial participation, particularly in the context of biomarker-matched trials of novel targeted therapeutics. 99…”
Section: Reduced Salience Of the Therapeutic Misconceptionmentioning
confidence: 99%
“…Of course, the prospect of therapeutic benefit will still vary considerably between trials according to phase (I-III), disease, and therapeutic mechanism (e.g., cytotoxics, targeted therapeutics, immunotherapeutic, and combination approaches), and, even within therapeutically oriented trials, every participant could not expect to benefit. 98 Nevertheless, patients considering participation in modern clinical trials, including earlyphase designs, might now be affirmed, at least to some extent, in expectations of benefit from trial participation, particularly in the context of biomarker-matched trials of novel targeted therapeutics. 99…”
Section: Reduced Salience Of the Therapeutic Misconceptionmentioning
confidence: 99%
“…125 Furthermore, we explored the superiority that this inflated value may imply for the selected group and what effects that might have on the other people who end up in 'the molecularly unstratified group'. 126 We made an application to the Wellcome Trust (London, UK) for a multidisciplinary analysis of this area, which unfortunately was not supported. This interest in the well-being of patients extended to a concern for those staff running studies, which revealed an interesting mixture of excitement, sense of privilege and unending stress for the personnel working in the trials unit on major platform studies of this nature.…”
Section: Patient and Public Involvement Perspectivesmentioning
confidence: 99%
“…Similar hype has plagued the human genome-precision medicine field [ 73 ]; genome-wide association studies have succeeded in demonstrating that very few chronic diseases are mediated by genes alone. Moreover, creating a distinction between groups of patients based on select biomarkers can leave large groups (so-called “molecularly unstratified” patients) without the “hope” of a particular intervention, and interfere with providing equitable access to care for all patients [ 74 ].…”
Section: An Example and A Cautionary Talementioning
confidence: 99%